2004
DOI: 10.1017/s026646740300107x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat segregation in two congeneric hawk-eagles (Spizaetus bartelsi and S. cirrhatus) in Java, Indonesia

Abstract: Habitat segregation in two congeric hawk-eagles (Spizaetus bartelsi abd S. cirrhatus) in Java, Indonesia Nijman, V. Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the material inaccessible and/or remove it from the website. Please Ask the Library: http://uba.uva.nl/en/contact, or a letter to: Library of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
0
17
0
2
Order By: Relevance
“…Although a wealth of primatological research has been conducted in Asia (see reviews in Campbell et al 2007) as indicated by Janson (1998) the most direct method to explore the impact of predation on primate populations is to conduct studies of the predators themselves that would reveal the prey profiles for each predator. Spizaetus hawkeagles are notoriously difficult to observe in the rainforest, and may be rare (Nijman 2004b;van Balen et al 2000). Thiollay (1985) estimated that on average he observed only one raptor day -1 while walking slowly inside the rainforest.…”
Section: Discussionmentioning
confidence: 99%
“…Although a wealth of primatological research has been conducted in Asia (see reviews in Campbell et al 2007) as indicated by Janson (1998) the most direct method to explore the impact of predation on primate populations is to conduct studies of the predators themselves that would reveal the prey profiles for each predator. Spizaetus hawkeagles are notoriously difficult to observe in the rainforest, and may be rare (Nijman 2004b;van Balen et al 2000). Thiollay (1985) estimated that on average he observed only one raptor day -1 while walking slowly inside the rainforest.…”
Section: Discussionmentioning
confidence: 99%
“…Kawasan penyangga kedua kawasan konservasi tersebut adalah hutan lindung, hutan produksi dan ladang masyarakat yang menyediakan habitat tambahan untuk elang jawa. Thiolay & Meyburg (1988) menyatakan bahwa elang jawa bergantung pada hutan primer, namun Nijman (2004) menyatakan bahwa daerah jelajah elang jawa bisa mencakup daerah-daerah terbuka di sekitarnya. Hal ini sesuai dengan elang jawa di kawasan CA Gunung Picis dan CA Gunung Sigogor yang juga memanfaatkan kawasankawasan di sekitarnya sebagai area berburu dan berinteraksi dengan lingkungannya.…”
Section: Hasil Dan Pembahasanunclassified
“…2000), di mana ada hubungan yang jelas antara pemanenan kayu dengan perburuan (Bennett dan Gumal, 2001). Pengaruh dari perburuan juga dilaporkan dari Kalimantan (Nijman 2004(Nijman , 2005Marshall dkk. segera terbit) dan diambil dari pengamatan pertama di kawasan hutan dengan tekanan perburuan mulai dari tingkat rendah hingga tinggi (Meijaard, pengamatan pribadi).…”
Section: Pola Umumunclassified